Prenatal SSRI/SNRI Exposure Does Not Lead to Childhood Seizures: How a Negative Study Can Enhance Clinical Care. (7th June 2022) - Berg, Anne T.; Glass, Torin
Abstract : The use of medications and other substances during pregnancy has long been a focus in obstetric care due to the concerns of both structural–anatomical (e.g., thalidomide, 1 valproic acid 2 ) and neurobehavioral (e.g., fetal alcohol spectrum disorder, 3 valproic acid 4 ) teratogenesis. In the case of a medical indication such as anxiety or depression, it is critical to know the risks and benefits of a therapy. Potential harm to the fetus may argue against treating a mother with depression. On the other hand, untreated maternal depression has consequences for the mother, and may have longer-term consequences for the child's social and cognitive development. 5, 6 Selective serotonin and norepinephrine reuptake inhibitors (SSRI/SNRI) are classes of drugs that have seen a substantial increase in their usage in pregnancy in response to a heightened awareness of maternal depression and anxiety. SSRI/SNRI medications, however, cross the placenta and act directly upon the brain of the neonate. They have been demonstrated to have serotonergic CNS effects 7 and are associated with an observable withdrawal syndrome that may be seen in the neonate following in utero exposure. 8 In addition to the behavioral and cognitive effects that fetal and early medication exposure may have on the developing brain, concerns about the development of neonatal and early childhood epilepsy have also been raised in association with maternal use of antidepressants and anxiolytics during pregnancy. 9